2022
DOI: 10.1021/acsapm.2c00843
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Amine-Functionalized ZIF-8 Mixed-Matrix Membranes with an Engineered Interface and Transport Pathway for Efficient Gas Separation

Abstract: Herein, we report a facile approach to engineer a metal–organic framework (MOF) structure and polymer–MOF interface in a mixed-matrix membrane (MMM) to achieve high gas separation performance and plasticization resistance. Hierarchical ZIF-8-NH2 nanoparticles with a relatively small concentration of amine functionality (∼5 mol %) were prepared. The hierarchical MOF structure provides fast molecular transport pathways because of the MOF–MOF percolated network and high MOF packing density. Moreover, the interfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…The average pore size of ZIF-8@CPA composite aerogel gradually decreased from 13.56 to 7.71 μm with the increase of ZIF-8. Due to the porosity of ZIF-8, the average pore diameter of the aerogel decreases, and it also can be observed from the SEM . We can see the homogeneous honeycomb porous structure and fiber assembly with ZIF-8 nanoparticles and multilayer micronanostructure composed of a 3D network of a porous structure bring a smaller size and decrease the average pore size distribution (Figure S2c).…”
Section: Resultsmentioning
confidence: 76%
“…The average pore size of ZIF-8@CPA composite aerogel gradually decreased from 13.56 to 7.71 μm with the increase of ZIF-8. Due to the porosity of ZIF-8, the average pore diameter of the aerogel decreases, and it also can be observed from the SEM . We can see the homogeneous honeycomb porous structure and fiber assembly with ZIF-8 nanoparticles and multilayer micronanostructure composed of a 3D network of a porous structure bring a smaller size and decrease the average pore size distribution (Figure S2c).…”
Section: Resultsmentioning
confidence: 76%
“…The incorporation of rigid MOF nanoparticles in the polymer matrix restricted the polymer chain mobility, thereby suppressing the plasticization behavior. 13 Figure 10b shows the normalized CO 2 permeability of the PI and ionic cross-linked BrMIL@BrPI-1 MMMs with various MOF weight loadings (10,20,30, and 40 wt %) as a function of CO 2 gas pressure. The ionic cross-linked BrMIL@ BrPI-1 MMMs exhibited further improvements in CO 2 plasticization resistance, and the plasticization resistance point increased to up to 15 bar at 40 wt % MOF loading compared to those of the non-cross-linked BrMIL/BrPI-1 MMMs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…4 MOF nanoparticles have high internal/external surface area, tunable chemical functionalities, and high chemical/thermal stabilities. 4,12,13 Because of these beneficial features, MOF nanoparticles have been incorporated into a polymer matrix to obtain a mixed-matrix membrane (MMM). 14−17 In particular, MOF nanoparticles with high internal surface areas and welldefined pore architectures can enhance diffusion-based molecular transport, which can supplement the limitations of the pure polymer membranes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…One way to address this issue is to increase the loading of MOF particles to above a so-called percolation threshold [typically above 30 weight % (wt%)] to form a percolation network (29)(30)(31). For instance, Su and co-workers (29) have found that when the UiO-66-NH 2 loading in the polysulfone membrane was increased from 30 to 40 wt%, a sudden boost of CO 2 permeability from 18 to 46 Barrer was observed, while the CO 2 /N 2 and CO 2 /CH 4 selectivities remained the same.…”
Section: Introductionmentioning
confidence: 99%